Adherence to clinical practice guidelines on community acquired pneumonia and its relation to mortality rates. - María Caridad Fragoso Marchante; Alfredo Darío Espinosa Brito; Gustavo Álvarez Amador; Iris González Morales; José Luis Bernal Muñoz; Miguel Mosquera Fernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: Community acquired pneumonia is a common disease that is associated with significant morbidity and mortality rates. In the General University Hospital ´´Dr. Gustavo Aldereguía Lima¨ in Cienfuegos, there are guidelines for the management of patients with community-acquired pneumonia, but no studies have been conducted as to the relation between their compliance and the mortality rate. Objective: To assess the adherence to guidelines for diagnosis and treatment of community-acquired pneumonia and its relation to mortality in hospitalized patients. Methods: A descriptive, observational and prospective case series study was conducted in all patients with a diagnosis of pneumonia or bronchopneumonia at the moment of admission and discharge from June 2006 to May 31, 2007. The relation between the different variables and the mortality rate was analyzed as to the different types of risks and the overall compliance with the guidelines for each risk with mortality. A multivariate analysis (logistic regression) was performed, with a 95% confidence interval. Results: The results are presented in tables of numbers and percent. Variables independently associated with mortality were: age (over 65 years old people), radiological lesions in more than one lobe or bilateral, atypical pneumonia debut, negative assessments as to the adherence to guidelines and inadequate treatments. Conclusion: The variables included in the study were enough to explain the final outcome of the patients, so it could be determined, for the first time in Cienfuegos, that the non-compliance with the guidelines of good clinical practice is related to mortality rates.